Neurocomputational mechanisms at play when weighing concerns for extrinsic rewards, moral values, and social image - Qu, Chen; Météreau, Elise; Butera, Luigi; Villeval, Marie Claire; Dreher, Jean-Claude (PLOS Biology, 2019)
Distinct brain systems are engaged when weighing whether to earn money by contributing to a ‘bad cause’ and when weighing whether to lose money to contribute to a ‘good cause,’ regardless of whether such choices are made privately or in public.